Genetic Diversity of Antifungi-Producing Rhizobacteria of Pseudomonas sp. Isolated from Rhizosphere of Soybean Plant - SUSILOWATI1 SUSILOWATI1; ARIS TRI WAHYUDI; YULIN LESTARI; SURYO WIYONO; ANTONIUS SUWANTO (Microbiology Indonesia, 2010)
Antifungi-producing rhizobacteria have been recognized playing an important role in plant disease suppression. In our laboratory, 13 indigenous soybeans' rhizobacteria Pseudomonas sp. that showed strong growth inhibition of root pathogenic fungi, Rhizoctonia solani, Fusarium oxysporum and Sclerotium rolfsii, have been isolated from rhizosphere of soybean plant. For further understanding, the genetic diversity of the antifungi-producing Pseudomonas sp. was investigated using Amplified 16S rDNA Restriction Analysis (ARDRA) and 16S rRNA gene sequences analysis. 16S rDNA were amplified by PCR technique and digested with restriction endonuclease HaeIII, RsaI and AluI. Sequences of 16S rRNA gene were analyzed using the BLAST program for similarity searches on sequence databases. ARDRA based dendrogram analysis was carried out by neighbor-joining of TREECON 1.3b software package. ARDRA indicated the variability of Pseudomonas sp. based on the digestion sites. Dendrogram clustering analysis based on the restriction enzymes profile of the amplified rDNA distinguished Pseudomonas sp. into 7 ribotype groups. The sequences of 16S rRNA gene confirmed that the isolates belonging to Pseudomonas sp. and the phylogenetic tree formed 4 clusters. There was a quite overlap among ARDRA groups and 16S rRNA sequence clusters. This finding suggested that antifungal producing Pseudomonas sp. were present in the rhizosphere of soybean plant and the level of genetic diversity exist within these species. Sequence analysis of the 16S rRNA gene of the Pseudomonas sp. with an identical ARDRA pattern confirmed that members of an ARDRA group were closely related to each other.